World Bank Group Climate Change Action Plan 2016–2020 : Retrospective - World Bank Group (World Bank, Washington, DC, 2020)
The Climate Change Action Plan 2016-2020 (CCAP) Retrospective presents the key achievements from the CCAP and the targets contained therein, including for climate finance. The report includes a comprehensive look at some of the initiatives that helped the World Bank Group meet and exceed these targets. The Retrospective is structured around the four strategic priorities of the CCAP, which closely mirror how efforts were structured. These are: Support transformational policies and institutions; Leverage resources; Scale up climate action; and Align internal processes and work with others.